2018
DOI: 10.1371/journal.pntd.0006458
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of co-administered ivermectin plus albendazole for treating soil-transmitted helminths: A systematic review, meta-analysis and individual patient data analysis

Abstract: BackgroundThe soil-transmitted helminths (STH), Ascaris lumbricoides, Trichuris trichiura and hookworms, infect 1.5 billion people worldwide and cause an estimated burden of 3.3 million disability-adjusted life years (DALYs). Current control strategies focus on morbidity reduction through preventive chemotherapy (PC) but the most commonly used recommended drugs (albendazole and mebendazole) are particularly inefficacious against T. trichiura. This, together with the threat of emerging drug resistance, calls fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 55 publications
(126 reference statements)
4
63
0
Order By: Relevance
“…Whilst shortening the time between MDA rounds may limit reestablishment of all STH species, if a single dose of albendazole is the treatment strategy in STH MDA programmes, the prevalence of T . trichiura will not be adequately reduced [37,38]. Research is ongoing into the efficacy of co-administrations with anthelminthics such as moxidectin, ivermectin or tribendimidine to target T .…”
Section: Discussionmentioning
confidence: 99%
“…Whilst shortening the time between MDA rounds may limit reestablishment of all STH species, if a single dose of albendazole is the treatment strategy in STH MDA programmes, the prevalence of T . trichiura will not be adequately reduced [37,38]. Research is ongoing into the efficacy of co-administrations with anthelminthics such as moxidectin, ivermectin or tribendimidine to target T .…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility to increase efficacy against T. trichiura infections may be the combination treatment with albendazole or mebendazole, 41,42 which seems promising, even though the cure rates for T. trichiura infections remain moderate. 43,44 Ivermectin is, however, known to be effective against other (soil-transmitted) helminths like Ascaris lumbricoides and Strongyloides stercoralis in children 30 and adults, 45 and in lower concentrations (following a dose of 150 μg/kg) also against onchocerciasis in children and adults. 1,24,35 With the proposed dose regimen of Table 2, equivalent exposure coverage can be achieved across pediatric age groups, providing a scientific rationale for adequate ivermectin dosing which is expected to improve treatment of these types of helminthiasis.…”
Section: Discussionmentioning
confidence: 99%
“…[13,14] Ivermectin is also efficacious against two other neglected tropical diseases endemic in Fiji, scabies and soil-transmitted helminths (STH). [2,[15][16][17][18] A national survey of scabies in 2007 found that all age groups and regions of Fiji are affected, with an estimated national prevalence of 18.5%. [16,19] Soil-transmitted helminths are also common in Fiji with a prevalence as high as 45% in school-aged children.…”
mentioning
confidence: 99%
“…Successful treatment of scabies and STH is expected to induce mild and transient symptoms primarily pruritus (scabies) and abdominal pain (STH). [16,18] We aimed to evaluate the safety of IDA in Fiji, providing a detailed account of AEs following DA and IDA mass drug administration in Fiji and an analysis of factors associated with their occurrence including filariasis, scabies, and STH infections.…”
mentioning
confidence: 99%